Hubungan Pendidikan Karakter dengan Hasil Belajar Tematik Siswa Kelas V SD Inpres 12/79 Macanang - nurmita Janna; Rosmalah Rosmalah; Makmur Nurdin (Universitas Negeri Makassar, 2021)
The problem in this study is the lack of students' understanding of the values of good character so that they appear less grateful, disciplined, polite, responsible, confident, caring, curious, independent, and creative. This study is a quantitative study with a correlation design that aims to determine the relationship between character education and thematic learning outcomes of fifth grade students of SD Inpres 12/79 Macanang. The results showed that there was a significant relationship between character education and thematic learning outcomes of fifth grade students of SD Inpres 12/79 Macanang with (4.8840) greater (>) the value of (1.67528) which means is rejected and is accepted. Based on the analysis of the data above, it can be said that character education will have an impact on the mindset of students in learning so that it will affect their learning outcomes in class. So, a good increase in the application of character values will improve student learning outcomes. from these conclusions, the impact resulting from this study is known that good character education will improve student learning outcomes.